Networking Salt Inducible Kinase 1 Regulatory Perturbations on Type 2 Diabetes- Breast Cancer Co-Morbidity Associated Molecular Bridge - Durrani I.A.; John P.; Bhatti A. (The EuroBiotech Journal)
Type 2 diabetes mellitus (T2DM) is associated with a 16% elevated risk of breast cancer (BC). However, the underlying molecular mechanisms are yet to be fully understood. T2DM and BC are multifactorial and polygenic in nature, hence it is plausible an interplay between various signalling pathways be wired into the co-morbidity program. Salt inducible kinase 1 (SIK1) was previously validated in silico as a hub gene for T2DM-BC molecular crosstalk. To probe into its functional niche within the co-diseasome, this study constructed and subjected SIK1 associated regulome to network modelling. Gene mutations, and transcription factors (TF), hub proteins and microRNA (miRNA) associated with SIK1 and its protein-protein interactions (PPIs) were extracted from MuTarget and EnrichR, respectively. TF-miRNA regulatory network iteration was studied on Cytoscape, to identify SIK1 associated 143 PPIs. Interestingly, these were enriched for KEGG pathways PI3K-AKT signalling, and pathways in cancer. Furthermore, ClinVar disease terms particularly included T2DM and BC, highlighting their potential implication in co-morbidity. Top hub genes included TP53, EP300, AKT1, CREB1, HIF1A, EGFR, SMARCA4, HDAC2, NFKB1 and HDAC5. Prospective studies on potentiating these hub genes particularly TP53, in context to SIK1 molecular dynamics may provide further insights into the molecular links tying T2DM to BC.